Tourists' perception towards pedestrian facilities : a case study of bintang walkway, Kuala Lumpur, Malaysia - Aljaberi, Shaikhah Saoud Abdullah (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2013)
Bukit Bintang is one of the most significant attraction destinations in Kuala Lumpur. This area is famous with its landmarks and shopping district with variety of commercial attractions. In such a crowded urban tourism destination with a huge number of people and vehicles had caused a certain issues that influence on pedestrian convenience and comfortability to move easily at the area. This study was conducted to explore tourists' perception who visited Bukit Bintang between Feburary and March 2013. The study aim is to identify the strengths and weaknesses of the existing pedestrian walkway at Jalan Bukit Bintang, to examine tourists' level of satisfaction after visiting the study area and the effect of tourists' demography on their perception. The most important components of the pedestrian facilities had covered in this paper such as connectivity, safety and amenities. A structured questionnaire was used to examine the facilities impact on tourists' perception. The questionnaire was distributed along the pedestrian walkway at Bukit Bintang targeted a sample of 80 tourists, 30 were local tourists and 50 were international tourists. The survey was conducted at different main shopping attractions at Bukit Bintang that are highlighted hereinafter. Findings reveal that respondents did not take any action toward the pedestrian circulation at the study area; however, they were satisfied in relation to the connection between the main attractions, lightings and pavements. Furthermore, they were dissatisfied with the signal time pedestrian crossing at the area, signage, landscape, benches, shades, public toilet and disable facilities. Some demographic factors (e.g. region, gender and age) were also found that it did not affect respondents' perceptions of pedestrian facilities. Partial pedestrian zone is recommended to achieve a success street shopping zone such as in Nuremberg Street. Also, there is a need to improve the safety elements such as bollards and signal pedestrian crossing time, and improve the pedestrian amenities, namely, shades, signage, benches, disable facilities and public toilet because they were rated very poor by respondents. The study helped to explore the pedestrian walkway facilities issues at the study area. This study generates a clear understanding of Bintang pedestrian walkway challenges and opportunities.